2002
DOI: 10.1603/0022-0493-95.3.531
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Thiamethoxam on Three Species of African Termite (Isoptera: Termitidae) Crop Pests

Abstract: Thiamethoxam formulated as ACTARA 25 WG has been tested on three species of higher African termites: Trinervitermes trinervius Rambur, Odontotermes smeathmani Fuller, and Amitermes evuncifer Silvestri, which are pests of the principal tropical food crops (e.g., rice, maize, sorghum, sugarcane). The doses used ranged from 0.03 to 10 ppm. The effective dose for these termites was 0.3 ppm, which resulted in 100% mortality within 2-8 d, depending on the species studied. Excluding O. smeathmani, which consumed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Time to attain > 50% and > 90% mortality was 5–9 and 7–12 days of exposure, respectively, for all three species. These values are close to those reported for higher species of African and Brazilian termites (Delgarde and Lefevre 2002a, 2002b) and for imidaclopid, a first generation neonicotinoid compound closely related to thiamethoxam (Gahlhoff and Koehler 2001), but higher than those reported for Coptotermes formosanus and Reticulitermes flavipes (Remmen and Su 2005a). These results suggest a difference in thiamethoxam resistance between higher and lower species of termites.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Time to attain > 50% and > 90% mortality was 5–9 and 7–12 days of exposure, respectively, for all three species. These values are close to those reported for higher species of African and Brazilian termites (Delgarde and Lefevre 2002a, 2002b) and for imidaclopid, a first generation neonicotinoid compound closely related to thiamethoxam (Gahlhoff and Koehler 2001), but higher than those reported for Coptotermes formosanus and Reticulitermes flavipes (Remmen and Su 2005a). These results suggest a difference in thiamethoxam resistance between higher and lower species of termites.…”
Section: Resultssupporting
confidence: 86%
“…Thiamethoxam has a wide spectrum of activity against aphids, whiteflies and leafhoppers (Senn et al 1998). It has also been reported to be non-repellent and has anti-feeding action against higher species of African termites (Delgarde and Lefevre 2002a). Recent studies showed that thiamethoxam was toxic and provided effective barrier against the Formosan subterranean termite ( Coptotermes formosanus Shiraki) and the eastern subterranean termite ( Reticulitermes flavipes Kollar) (Remmen and Su 2005A, 2005b).…”
Section: Introductionmentioning
confidence: 99%
“…14) Several chloronicotinyl insecticides such as imidacloprid and thiamethoxam have been studied extensively for the control of subterranean termites. 15,16) Boucias et al 17) reported that imidacloprid treatment caused workers of R. flavipes to become sluggish, inhibited grooming and tunneling, and eventually caused death. In our tests, workers of R. flaviceps, C. formosanus and O. formosanus treated with acetamiprid showed similar symptoms of poisoning.…”
Section: Anti-tunneling Effect Of Acetamiprid On Worker Termitesmentioning
confidence: 99%
“…Any modiWcation to the chemistry of starch or carbohydrates or its palatability to the beetles due to the presence of the thiamethoxam may have some anti-feeding aVect on D. minutus. Thiamethoxam had been reported to have anti-feeding eVect on crop pests and subterranean termites (Delgarde and Lefevre 2002a;Acda 2007). In contrast, low doses of thiamethoxam (<1.0 g ml ¡1 ) did not prevent beetle oviposition and the larvae were able to pupate and emerge as adults.…”
Section: Discussionmentioning
confidence: 96%